Bringing Sociology Closer to Students: Teachers’ Initiatives for Contextual and Meaningful Learning - Mujayapura, Muhammad Retsa Rizaldi; Komariah, Siti (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study aims to examine sociology teachers’ initiatives in implementing contextual and meaningful learning at the senior high school level. Using a qualitative descriptive approach, data were collected through classroom observations and in-depth interviews with sociology teachers in Bandung and Cimahi. The findings reveal four key themes: differentiated instruction, inclusive classroom management, contextual transformation of sociological concepts, and creative use of media and methods. Teachers demonstrated sensitivity to students’ social backgrounds, interests, and learning stages, linking abstract theories to current social issues and real-life experiences. These practices fostered participatory learning, critical reflection, and deeper student engagement. The study underscores the essential role of teachers in creating inclusive and transformative learning spaces where sociology is not only taught but lived.